The Kingfisher soccer encyclopedia - Gifford, Clive (Gifford, Clive. Kingfisher encyclopedias., 2014)
This encyclopedia is the definitive guide to the world's most popular sport. From the sublime skills of Pele to the lifestyle of a professional soccer player, this gloriously illustrated book explores every aspect of the game. Freshly revised and updated, this is a world soccer book for the 2014 World Cup and beyond.